ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN (STUDI KASUS CV.DELTA GLASS JL. S. PARMAN NO.15,MEDAN) - Ferdy Aresta; Winda Sri Astuti Doloksaribu; Fernando Fedrian; Christian Wijaya; Erwina (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study was conducted to analyze the factors influencing purchasing decisions (case study of CV. Delta Glass, S. Parman Street No. 15, Medan). The respondents in this study were 30 employees of CV. Delta Glass. The research utilized SMART PLS data processing to determine the validity and reliability of variables and to examine whether each independent variable positively or negatively affects the dependent variable. The results of this study show that the endorsement variable does not partially influence purchasing decisions, with a T-statistic value (1.193) less than 1.96, and a P-value (0.234) greater than 0.05. The price variable partially influences purchasing decisions, with a T-statistic value (2.797) exceeding 1.96, and a P-value (0.014) less than 0.05. Therefore, hypothesis H2 can be accepted. The service quality variable partially influences purchasing decisions, with a T-statistic value (2.461) exceeding 1.96, and a P-value (0.005) less than 0.05. Thus, it can be concluded that H3 can be accepted. However, in the F-test, it was found that the endorsement, price, and service quality variables simultaneously positively influence purchasing decisions, with an F-test value (0.471) exceeding 0.062.